Isolation of Microorganisms and Its Application for Decolorization of Anthraquinone and Azo Dyes from Textile Wastewater - Fathoni, Ahmad; Jeong, Soo Kyoung; Kim, Joon Kyun (Annales Bogorienses, 2013)
The treatment of textile waste water